2019
DOI: 10.1002/pmic.201800315
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Transcriptomic and Proteomic Analysis of Primary Human Umbilical Vein Endothelial Cells

Abstract: Understanding the molecular profile of every human cell type is essential for understanding its role in normal physiology and disease. Technological advancements in DNA sequencing, mass spectrometry and computational methods allow us to carry out multi-Omics analyses although such approaches are not routine yet. Human umbilical vein endothelial cells (HUVECs) are a widely-used model system to study pathological and physiological processes associated with the cardiovascular system. In this study, we employed ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 75 publications
0
10
0
Order By: Relevance
“…Compared with other relevant HUVEC/liver proteomics studies with strong cation exchange chromatography, our lower protein extraction efficiency in recellularized scaffolds should be improved in future study. 25,26 Furthermore, coculture of endothelial cells, pericytes, and smooth muscle cells may be an important strategy to further improve angiogenesis, myogenesis, and vascular function.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with other relevant HUVEC/liver proteomics studies with strong cation exchange chromatography, our lower protein extraction efficiency in recellularized scaffolds should be improved in future study. 25,26 Furthermore, coculture of endothelial cells, pericytes, and smooth muscle cells may be an important strategy to further improve angiogenesis, myogenesis, and vascular function.…”
Section: Discussionmentioning
confidence: 99%
“…However, the known interaction partners of Spire1—FMN1 and FMN2 [ 30 , 50 , 51 ]—appear not to be expressed in HUVEC in significant amounts at the RNA (Fig. S7) and protein level [ 16 , 52 ]. On the other hand, in invadosomes Spire1 seems to form a complex with mDia1 [ 34 ] and the human diaphanous homolog 1 was found to significantly associate with both Rab27a and Rab3b in HUVEC ( p < 0.05) [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, these molecules are receptor candidates of these cells for cytoadhesion of P. knowlesi -iRBCs. As for HUVECs, comprehensive proteomics analysis revealed that of the above mentioned 6 molecules the highest expressions observed were for PECAM1 (Peptide spectrum match (PSM) = 431), followed by ICAM1 (PSM = 59), and low expression of VCAM1 (PSM = 0.21); whereas CSPG4, P-selectin, and CD36 were not detected 23 . It would be of interest to examine if the first three molecules are receptors of SICA-HUVEC.…”
Section: Discussionmentioning
confidence: 99%